2016
DOI: 10.1186/s12936-016-1519-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing microscopic and submicroscopic malaria parasitaemia at three sites with varied transmission intensity in Uganda

Abstract: BackgroundParasite prevalence is a key metric used to quantify the burden of malaria and assess the impact of control strategies. Most published estimates of parasite prevalence are based on microscopy and likely underestimate true prevalence.MethodsThick smear microscopy was performed in cohorts of children (aged 6 month to 10 years) and adults every 90 days over 2 years, at three sites of varying transmission intensity in Uganda. Microscopy-negative samples were tested for sub-microscopic parasitaemia using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 32 publications
11
52
0
Order By: Relevance
“…The survey also uncovered six to tenfold higher rates of parasitaemia using a combination of LM and molecular techniques, highlighting high levels of previously unappreciated sub-microscopic parasitaemia [8]. In this study asymptomatic women did not have parasitaemia detectable by RDT, LM or PCR, implying that malaria rates may be low in the population.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The survey also uncovered six to tenfold higher rates of parasitaemia using a combination of LM and molecular techniques, highlighting high levels of previously unappreciated sub-microscopic parasitaemia [8]. In this study asymptomatic women did not have parasitaemia detectable by RDT, LM or PCR, implying that malaria rates may be low in the population.…”
Section: Discussionmentioning
confidence: 55%
“…A 2011–2013 community-based survey conducted in three Ugandan sub-counties with varied transmission settings performed the first rigorous assessment of malaria metrics in both children and adults [79]. According to the results of this survey, malaria prevalence based on LM ranged from 3.0 to 5.1% among adults aged ≥18, while prevalence based on both LM and molecular techniques ranged from 18.8 to 53.5% in the same age group [8]. This is one of the first detailed studies on the prevalence of malaria in adults, but additional data from other regions and broad age groups is needed to adequately monitor malaria trends in Uganda [10].…”
Section: Introductionmentioning
confidence: 99%
“…The DBLα domain is present in all var genes except the atypical, placental adhesion VAR2CSA. Typical of high transmission areas in West Africa, asymptomatic infections represent the majority of the P. falciparum parasite population across all age groups (28)(29)(30). While carrying parasites most of the time, children experience only one to five clinical episodes per year with 1-2% of these infections leading to severe clinical disease (31).…”
mentioning
confidence: 99%
“…Out of the 1,344 subjects enrolled, 44% were children under 5 years of age, 32% 5–10 years, and 24% above 18 years. Prior reports defined malaria transmission, prevalence, and incidence in the three cohorts, as summarized in Table 1 (Kamya et al, 2015; Rek et al, 2016). The sites differed markedly, with very high transmission intensity, parasite prevalence, and malaria incidence in Tororo District, lower levels of all of these parameters in Kanungu District, and the lowest levels in Jinja District.…”
Section: Resultsmentioning
confidence: 99%
“…To establish the cohorts, all households within the three sub-counties were enumerated and mapped, and randomly selected households that included at least one resident 0.5–10 years of age and one adult resident were enrolled, as previously described (Kamya et al, 2015). This study included cohort members reported previously and additional subjects recruited into the cohorts after prior reports (Kamya et al, 2015; Rek et al, 2016). Cohort household adults provided the primary language spoken by the household.…”
Section: Methodsmentioning
confidence: 99%